Proposed Quality Improvement of Liquid Organic Fertilitizers "Herbafarm" to Meet National Standards in Indonesia (The Indonesian Journal of Business Administration, 2012)
Indonesia is a country with abundant natural resources. It is supported with arable land and tropical climate that make agriculture, plantation and forestry in Indonesia is growing.In agriculture, fertilizer is an important commodity. Fertilizers are divided into two types, namely organic fertilizer and inorganic fertilizer.Understanding the importance of fertilizers for agriculture, the Ministry of Agriculture Republic of Indonesia has set standards of quality for fertilizers in Indonesia. Quality is usually defined as the characteristics of a product that include performance, reliability, and ease of use.This thesis background is report from Soil and Plant Laboratory Inc. about the lowness macronutrient content of Herbafarm.This final project is focused to find the cause of decreased quality of Liquid Organic Fertilizer "Herbafarm" and proposed the method to improve its quality. Methodology that used in this thesis is examining every activities related to production of its fertilizer. Beside that, it also analyzed the Quality Control data, measures production process performance from the data with the Control Chart, and use a fishbone diagram method to analyze the root problem. Also providing quality improvement proposals to meet the National standards by using Six Sigma approach.Result from the study is found inadequacies raw material warehouse that cause the decrease of raw material content. The proposed recommendation is to build new raw material warehouse according to minimum standard of material handling Keywords: Organic fertilizers, Quality, Raw material, Six Sigma